Stability of Organic Solar Cells: From Fullerene Derivatives to Non-fullerene Acceptors - Du, Xiaoyan; Guo, Jing; Min, Jie; Li, Ning (Organic Solar Cells: Materials Design, Technology and Commercialization, 2022)
The development of organic photovoltaic (OPV) technologies has reached a respective scientific level of understanding. The power conversion efficiency (PCE) of >18% has been demonstrated for lab-scale organic solar cells (OSCs), while large-scale organic solar modules (>200 cm 2) have achieved PCEs close to 12%. In order to continuously develop the OPV technologies toward commercialization, it is imperative to in-depth investigate the stability issues of OSCs under various conditions and to understand corresponding degradation mechanisms. The development of OSCs from fullerene derivatives to non-fullerene acceptors (NFAs) not only promotes the device performance to a significantly high level but also greatly changes the understanding of device stability, especially the microstructure stability of photoactive layers. In this book chapter, we first introduce the factors limiting the stability of OSCs, including extrinsic factors related to external stresses and intrinsic factors related to materials and devices. We summarize the stability evaluation protocols based on the test guidelines introduced by the International Electrotechnical Commission (IEC) and the International Summits on Organic PV Stability (ISOS). We focus our efforts on the development of stable OSCs based on different acceptors and summarize in detail the effective strategies to enhance the microstructure stability of OSCs. We hope that this work can arouse more attention in the community to the stability of OSCs and can contribute to the development of next-generation OSCs with excellent device performance as well as excellent operational stability, which is required for large-scale production and commercial applications.
CRIS-Team Scopus Importer:2024-12-16